Problems of Small and Medium Business in Germany - B. E. Zaritskiy (Vestnik MGIMO-Universiteta, 2020)
The article deals with the problems of small and medium entrepreneurship (SME) in Germany, its role in the country’s economy. It reveals the mechanism of interaction of government structures, political parties, business alliances and the expert community in formulating and carrying out policies aimed at supporting SME. It shows that real business conditions in Germany differ substantially from what is usually offered to potential investors in advertising brochures. The Total Early-Stage Entrepreneurial Activity Index (TEA-Quote) puts Germany far behind its competitors. For several consecutive years the number of liquidated small and medium enterprises has been higher than that of newly created ones. Germany’s new generation prefers to seek jobs in big companies or in the civil service. Germany seems to have lost the Gründer spirit. Entrepreneurs complain about the great number of bureaucratic procedures, the growing shortage of skilled workforce, high electricity prices, and difficulties in accessing bank credits for micro and small enterprises. An underdeveloped market of venture capital has been a drag on innovative startups. A successful cluster policy, which gave a new impulse to the development of several territories, has not offset serious shortcomings in the country’s entrepreneurial climate. While not dramatizing the situation, the author considers as mistaken a common point of view found in Russian publications. This point of view holds that framework conditions for business in Germany constitute a near-ideal model, which leads to success as long as it is copied faithfully. The article analyses public discussion in Germany about the problems of SMEs, complains of small and medium business against the authorities. The key provisions of the government strategy to develop small and medium business adopted in 2019 and a cessionary package to mitigate damage of the coronavirus outbreak on the German economy adopted in 2020 are reviewed. The main conclusion of the author is that the German experience should be treated selectively, taking into account overall internal political, economic and social conditions under which the German policy of supporting SMEs is designed. The strengths of this policy lie in its systemic nature and a commitment to align it with industrial, innovative, social, research, and educational policies.